Effect of Psychological Stress on the General Health of Young Adult Girls - Anjali; Zeba Jamal; Prachi Shukla; Akanksha Singh (Archives of Current Research International, 2024)
Stress is a condition of anxiety or mental fatigue brought on by difficult situation. Stress is prevalent among young girls. Psychological stress has been shown to have a significant effect on general health, particularly in young adults traversing a challenging stage of life marked by emotional, social, and intellectual obstacles. Young adult girls (ages 18 to 25) should pay special attention to this since they experience particular stressors from burgeoning careers, social expectations, body image concerns, and scholastic constraints. Given that stress has been connected to both physical and mental health issues, it is imperative that they comprehend how these stressors are affecting their overall health. This study aims to explore the effects of psychological stress on the general health of young adult girls by examining the relationship between stress levels and various health outcomes. The present study investigates the effects of mental stress on the general health of young adult girls. The study conducted in the Month of April-May 2024. Insight of the Study Data collection from 100 respondents (girls) from Acharya Narendra Deva University of Agriculture & Technology were gathered from a varied sample of young girls using a self-structured questionnaire (Google form). Descriptive research design was opted for the study. The study shows that 85% of girls get stressed and 46% of respondents suffer stress from career or family pressure. Sleeping (33%) is the major activity that is performed for the release of stress. 31% of girls suffer from irregular periods due to stress. The study also find that the diet of the respondents was also a major concern. The study concluded that there is significant relationship between mental stress and the health of young adult girls. Mental stress can be controlled through regular meditation and good sleeping patterns.